Let $(M,g)$ be a Riemannian manifold. Why does the following formula hold?

$$\operatorname{div} X= \tfrac12\,\mathrm{tr}_g\bigl(\mathcal{L}_Xg\bigr) $$

$\operatorname{div} X$ is defined by $ (\operatorname{div} X)\omega_g= d(i_X(\omega_g))$ where $i_X$ is interior multiplication by $X$.


Here is my tuppence worth. I hope it is what you are after and please excuse the perhaps unfamiliar notation - comments/questions/suggestions are welcome!

Let $M$ be a Riemannian manifold endowed with metric $g$ where

$$g \,=\, \delta_{ab}e^{a} \otimes e^{b}$$

with respect to a $g$-orthonormal coframe $\{e^{a}\}$. Denote the dual $g$-orthonormal frame $\{X_{b}\}$ (i.e. $e^{a}(X_{b})=\delta^{a}_{b}$). We introduce the operator

$$A_{X} \,\equiv\, \nabla_{X} - \mathcal{L}_{X}\quad \text{for any}\; X\in TM$$

in terms of the Levi-Civita connection $\nabla_{X}$ and Lie derivative $\mathcal{L}_{X}$. Note that since $\nabla_{X},\mathcal{L}_{X}$ commutes with contractions, so does $A_{X}$, and that for any function $f$ it should be clear that $A_{X}f=0$. In particular, for any $X,Y,Z\in TM$:

$$\begin{align}A_{X}[\,g(Y,Z)\,] \,=\, 0 &\,=\, (A_{X}g)(Y,Z) + g(A_{X}Y,Z) + g(Y,A_{X}Z) \\ &\,=\, -(\mathcal{L}_{X}g)(Y,Z) + g(A_{X}Y,Z) + g(Y,A_{X}Z), \end{align}$$

since $\nabla$ is metric compatible. Furthermore, since $\nabla$ is torsion-free, we can show $A_{X}Y=\nabla_{Y}X$. Putting all this together yields

$$(\mathcal{L}_{X}g)(Y,Z) \,=\, g(\nabla_{Y}X,Z) + g(Y,\nabla_{Z}X)$$

for any $X,Y,Z\in TM$. In particular, for $V\in TM$:

$$\begin{align} (\mathcal{L}_{V}g)(X_{k},X_{k}) \,=\, tr_{g}(\mathcal{L}_{V}g) &\,=\, g(\nabla_{X_{k}}V,X_{k}) + g(X_{k},\nabla_{X_{k}}V) \,=\, 2\,i_{X_{k}}\nabla_{X_{k}}\widetilde{V} \end{align}$$

where $\widetilde{X}=g(X,-)$ denotes the metric dual of any $X\in TM$ (we use the metric compatibility of $\nabla$ to get here). Thus we have

$$i_{X_{k}}\nabla_{X_{k}}\widetilde{V} \,=\, \frac{1}{2}tr_{g}(\mathcal{L}_{V}g)$$

Now for torsion-free $M$, we have

$$de^{a} + \omega^{a}_{\;b} \wedge e^{b} \,=\, 0$$

in terms of the connection 2-forms $\{\omega^{a}_{\;b}\}$ defined by:

$$\nabla_{X_{b}}e^{a} \,=\, -\omega^{a}_{\;c}(X_{b})e^{c}.$$

It is easy to show using these two relations that $d\equiv e^{a} \wedge \nabla_{X_{a}}$. Then using $\text{div}(V)=\star d\star \widetilde{V}$ in terms of the Hodge map $\star$:

$$\text{div}(V) \,=\, \star d\star \widetilde{V} \,=\, \star(e^{k} \wedge \nabla_{X_{k}}\star\widetilde{V}) \,=\,i_{X_{k}}\nabla_{X_{k}}\widetilde{V} \,=\, \frac{1}{2}tr_{g}(\mathcal{L}_{V}g) $$

where again you use the metric-compatibility of $\nabla$ to commute it with the Hodge map: $\nabla_{X}\,\star=\star\nabla_{X}$.

NB: If you are familar with it, you may notice that the object $i_{X_{k}}\nabla_{X_{k}}$ is, up to possibly a sign, related to the co-derivative $\delta$ on $M$. It should also be noted that most of this, again up to a possible sign, follows through for pseudo-Riemannian manifolds.

  • $\begingroup$ Thanks! Your solution is very elegant and beautiful. If I interpreted everything correctly, when you right $d\equiv e^{a} \wedge \nabla_{X_{a}}$ you refer to the exterior derivative and the (natural induced) connection on the space of $k$-forms on $M$, for some $k$. $\endgroup$ – Asaf Shachar Feb 26 '17 at 21:56
  • $\begingroup$ Yes - that's right! $\endgroup$ – AloneAndConfused Feb 26 '17 at 22:50

Fix a normal coordinate system $(x^1,\dots,x^n)$ centered at $p$ and write $X = X^i \partial_i$. Then (all calculations are evaluated only at $p$)

$$ \mathcal{L}_{\partial_i}{\partial_j} = \nabla_{\partial_i} \partial_j - \nabla_{\partial_j} \partial_i = [\partial_j, \partial_i ] = 0, \\ \mathcal{L}_X(\partial_j) = -\mathcal{L}_{\partial_j}(X^i \partial_i) = -\partial_j(X^i) \partial_i - X^i \mathcal{L}_{\partial_j}(\partial_i) = -\partial_j(X^i) \partial_i, \\ (\mathcal{L}_X g)(\partial_j, \partial_j) = Xg(\partial_j, \partial_j) - 2g(\mathcal{L}_X \partial_j, \partial_j) = 2g \left( \partial_j(X^i) \partial_i, \partial_j \right) = 2 \partial_j(X^i) \delta_i^j, \\ \frac{1}{2} \operatorname{tr}_g \left( \mathcal{L}_X g \right) = \frac{1}{2} \sum_{j=1}^n (\mathcal{L}_X g)(\partial_j, \partial_j) = \partial_j(X^j) = \operatorname{div}(X). $$

The latter formula for the divergence in a normal coordinate system can be verified similarly. Namely,

$$ d(i_X(\omega_g))(\partial_1, \dots, \partial_n) = \sum_{i=1}^n (-1)^{i-1} \partial_i ((i_X \omega_g)(\partial_1, \dots, \hat{\partial_i},\dots,\partial_n)) = \sum_{i=1}^n \partial_i \omega_g(\partial_1,\dots,\partial_{i-1},X,\partial_{i+1},\dots,\partial_n) = \partial_i (X^i) .$$


Maybe this isn't what you are looking for but it's fairly straightforward in coordinates.

\begin{equation} \mathcal{L}_{X} \left(g \right) = g_{ik} (\partial_j X^k) + g_{kj} (\partial_i X^k) + (\partial_{l} g_{ij}) X^l \end{equation} so

\begin{equation} \frac{1}{2} g^{ij} \mathcal{L}_{X} \left(g \right) = \frac{1}{2} g^{ij} g_{ik} (\partial_j X^k) + \frac{1}{2} g^{ij} g_{kj} (\partial_i X^k) + \frac{1}{2} g^{ij} (\partial_{l} g_{ij}) X^l = \frac{1}{2} \delta_{jk} (\partial_j X^k) + \frac{1}{2} \delta_{ki} (\partial_i X^k) + \Gamma_{li}^{i} X^l = \partial_k X^k + \Gamma_{li}^{i} X^l = \text{div} X \end{equation}

  • $\begingroup$ Given the definition of $\text{div}(X)$ as $(\text{div}(X))\,\omega_g = d(\iota_X(\omega_g))$, how do you know that $\text{div}(X) = \partial_kX^k + \Gamma^i_{\ell i} X^\ell$? $\endgroup$ – Jesse Madnick Feb 15 '17 at 22:56

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.